Autoantibodies and Malaria: Where We Stand? Insights Into Pathogenesis and Protection - Mourão, Luiza Carvalho; Cardoso-Oliveira, Gustavo Pereira; Braga, Érika Martins (Frontiers in Cellular and Infection Microbiology, 2020)
Autoantibodies are frequently reported in patients with malaria, but whether they contribute to protection or to pathology is an issue of debate. A large body of evidence indicates that antibodies against host-self components are associated to malaria clinical outcomes such as cerebral malaria, renal dysfunction and anemia. Nonetheless, self-reactive immunoglobulins induced during an infection can also mediate protection. In light of these controversies, we summarize here the latest findings in our understanding of autoimmune responses in malaria, focusing on Plasmodium falciparum and Plasmodium vivax. We review the main targets of self-antibody responses in malaria as well as the current, but still limited, knowledge of their role in disease pathogenesis or protection.